(untitled) (Bulletin of Innovative Research, 2026)
This article examines how the media form and disseminate new words (neologisms) in modern English. The study analyzes texts from television, online news, and social media to identify the structure and functions of new lexical units. The results show that the media, while reflecting language change, play an important role in the normalization and dissemination of neologisms, especially among the younger generation. The study highlights the dominance of English words, abbreviations, and Internet jargon in the media and demonstrates the importance of these texts in language education. The article examines in detail the mechanisms of neologism formation, their social and cultural impact, and the development of language under the influence of digital technologies. The results of the study confirm the active role of the media in language formation and provide suggestions for future research.